Women recharge: training and economic sanctuary for single mothers in Tumpat, Kelantan - Nik Aminuddin, Nik Farhana; Asif, Nayeem; Alias, Nur Ulfah Awatif Umairah; Denan, Zuraini (IIUM Press, 2025)
This paper focuses into the pivotal role of helping single mothers to grow not only emotionally but also in economic aspect. Single mothers represent a growing but marginalised group both in urban and rural area of Malaysia. Single mothers often face dual responsibilities as caregiver and breadwinner. Hence, this paper explores the architectural aspect which envisioned “training and economic sanctuary” in order to help single mother grow and give them a better chance to sustain their life. One of the main interest is to recognise the growing presence of women in micro businesses particularly in Kelantan, which emphasise on Batik and tailoring. However, a combination of modern entrepreneurship is needed which lead to the presence of digital training aligned with current modernisation. These activities encourage both the growth of single mothers and empower the area of Tumpat, Kelantan as main hub for Batik production.